Effect of micronutrients and bio-fertilizers on growth, yield and quality of kharif Groundnut (Arachis hypogaea L.): Effect of micronutrients and bio-fertilizers on growth, yield and quality of kharif Groundnut (Arachis hypogaea L.) - K YASWANTH ACHARI; A K GHOTMUKALE; K D DAHIPALE (Journal of Oilseeds Research, 2023)
A field experiment was carried out during rainy season-2021 at Experimental farm, Oilseeds Research Station, Latur, to evaluate the effect of zinc and bio-fertilizers on growth, yield and quality parameters of kharif groundnut (Arachis hypogaea L.) variety LGN-1. Application of RDF (25:50:00 NPK kg/ha) + ZnSO4 @ 20 kg/ha + Rhizobium @ 250ml/10 kg of seed + PSB @ 250ml/10 kg of seed (T7) produced higher growth, yield and quality traits along with good net returns and B:C ratio.